Earnings Management and Stock Market Returns - Amadi, Felicia Y; Amadi, Confidence W (International Journal of Business, Economics and Management, 2014)
This paper investigates the variability of real business activities in the form of discretionary expenditures (accounts receivable, selling, general and administrative expenses, and net change in accruals), and the firm’s stock price performance in relation to the frequency of meeting or beating analysts’ earnings forecast. In addition, the study investigated the relationship between the firm’s stock price performance, and the variability of these financial statement accounts. The objective was to examine if these selected financial statement of accounts could be used by management to manipulate earnings in order to meet and/or beat analysts’ earnings forecasts so as to enhance the firm’s stock performance. The study found that there is a significant difference between the variance of SG&A, NCA and stock returns of the firms that meet and/or beat the analysts’ forecast and those that do not. It was also found that there is a significant difference in stock returns based on meeting and/or beating the analysts’ estimate.